Achieving thermal comfort and sustainable urban development in accordance with the principles of bioclimatic architecture: A case study of Ulcinj (Montenegro) - Bajçinovci, Bujar (Quaestiones Geographicae, 2017)
Human communities have always taken actions to create a healthier environment for living and working. Those efforts are best documented in the architectural structure everywhere, starting from ancient history to the present. It is assumed that the town of Ulcinj is one of the earliest cities on the Adriatic coast. The building morphology and urban structure of Ulcinj is 2,500 years old and is continued by multi-ethnical society. Hence, the urban structure of Ulcinj developed harmonically across the rock hills which encompass the city beach, forming the urban structure which is perceived as the unity of land and sea. The study investigates the Ulcinj urban structure, urban management, sustainable development, focusing on human comfort, and environmental actions with a view to accomplish better and more natural life. Bioclimatic passive design principles are associated with an environmental sustainable design, interrelated to the microclimate of the region, connected to the thermal, spatial, visual, acoustic, and air quality. The research method consists of empirical observation through the city and riviera. According to the conceptual findings of this paper, with a proper implementation of bioclimatic passive principles, the work seeks to indicate that it is possible to achieve a higher level than the current one. Hence, the huge number of tourists and overnight stays can make a difference in eco-tourism, and sustainable development if we can achieve energy efficiency, and preserve the natural resources in accordance with passive bioclimatic principles.